(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
Plastic pollution has an effect on marine waters and limited information about the impact on the digestive tracts of migratory fish. Therefore, this study aims to analyze the content of microplastics in the digestive system of fish that are located in the intestines and identify the type of microplastic polymers in the meat of big-eyes tuna fish landed in the port of Wakatobi fish. The research was conducted from March to July 2020 in Wakatobi Regency. The process of identifying the microplastic content in the intestines of bigeyes tuna was carried out in 4 stage, namely (1) fish disscetion, (2) density separation, (3) removal of organic compounds, (4) visual observation. Identification of the type of microplastic polymers in meat of bigeyes tuna was analyzed using fourier transform infrared (FTIR). The results showed that there are microplastics in the intestines of big-eyes tuna fish numbering twelve particles with microplastic types in the form of blue, brown and red fibers. The size of microplastic which found was 0.701-4.305 mm. The results of FTIR analysis on fish meat showed polyethylene compounds marked by the presence of C=O stretch bonds.